Families in Austronesian Expansion. (July 2019) - Wellen, Kathryn
This article looks at the possibility of using family as an analytical tool for understanding large-scale historical processes. The case in point is Austronesian expansion which is conceived of here within the largest possible geographical and chronological contexts to include the prehistoric spread of Austronesian speakers from Madagascar to Hawaii and twenty-first-century migration patterns and transnational lifestyles. It explores the possibility of using family relations as an analytical tool for making sense of this exceptionally vast subject. It also argues that an understanding of Austronesian expansion is essential to an understanding of world history.